Drawing the Line: Criminal Responsibility of In-House Legal Counsel - Febriyani, Febriyani; Prasetyo, Boedi (Jurnal Ilmu Hukum Kyadiren, 2026)
The criminal prosecution of in-house legal counsel in corporate cases has generated significant debate concerning the boundaries of criminal liability within the legal profession in Indonesia, particularly where legal opinions serve as the basis for corporate policy decisions. This study examines the legal limits of criminal liability for in-house legal counsel, evaluates the legal character of legal opinions in relation to the concept of deelneming, and critically analyzes the judicial reasoning in Decision Number 534/Pid.B/2024/PN Jakarta Selatan. Employing a normative legal research method with statutory, conceptual, and case-based approaches, this study finds that the criminal liability of in-house legal counsel is determined by causal contribution and substantive intent rather than by formal position alone. Legal opinions may give rise to criminal liability when they function as instruments of legitimacy for unlawful conduct. The study concludes that the decision adopts a functional approach to professional legal accountability and underscores the necessity of clear normative boundaries to prevent the excessive criminalization of in-house legal counsel.